Pathogens Detected in Questing Ixodes ricinus Ticks in a Mountainous Area in Greece - Tsioka, Katerina; Saratsis, Anastasios; Pappa, Styliani; Papa, Anna (Pathogens (Basel), 2024)
Ixodes ricinus ticks are vectors of a plethora of pathogens. The purpose of this study was to screen 398 I. ricinus ticks for a variety of pathogens. Following the pooling, homogenization, and extraction of total nucleic acids, a real-time PCR was applied for the detection of a panel of tick-borne pathogens, while additional conventional PCRs combined with Sanger sequencing were applied for the detection of viruses and typing of Rickettsia and Borrelia species. At least one pathogen was detected in 60 of the 80 (75%) tick pools. Rickettsia spp. predominated, as it was detected in 63.75% of the pools (51/80; MIR 12.81%), followed by Borrelia spp. (35 pools (45%); MIR 8.79%), while Anaplasma phagocytophilum was detected in 2 pools (2.5%, MIR 0.5%). The ticks of six Rickettsia-positive pools were tested individually (from stored half-ticks); all sequences were identical to those of R. monacensis. Similarly, the ticks of six Borrelia-positive pools were tested individually, and it was shown that four belonged to the genospecies Borrelia garinii and two to Borrelia valaisiana. Phleboviruses were detected in 3 pools (3.75%; MIR 0.75%), with sequences clustering in the Ixovirus genus, while nairoviruses were detected in 7 pools (8.75%; MIR 1.76%), with one sequence clustering in the Orthonairovirus genus, and six clustering in the Norwavirus genus. Although a small number of ticks from only one area in Greece were tested, a variety of pathogens together with recently identified viruses were detected, prompting further studies in ticks and surveillance studies in humans.